Thrombolytic Therapy in Normotensive Patients with Pulmonary Embolism (Data from the Retrospective Study) - N. A. Сherepanova; I. S. Mullova; A. R. Kiselev; T. V. Pavlova; S. M. Khokhlunov; D. V. Duplyakov (Рациональная фармакотерапия в кардиологии)
Background. The thrombolytic therapy is absolutely recommended for patients in shock or hypotension because the benefits are clearly outweighing the risks. However, in hemodynamically stable patients, including those with acute right ventricular dysfunction and/or myocardial damage, thrombolysis has a significantly lower evidence level.Aim. To study the criteria based on which doctors decide to conduct thrombolytic therapy in normotensive patients in real clinical practice according to the retrospective data.Material and methods. A single-center retrospective cohort study analyzed medical records of patients hospitalized in 2006-2017 with a verified diagnosis of pulmonary embolism (PE) and who had a systolic blood pressure >90 mm Hg at the time of admission.Results. The present study population included 299 patients with a verified diagnosis of PE from 2006 to 2017 years. Patients were divided into two groups: with thrombolysis (group 1) and without thrombolysis (group 2). Logistic regression analysis showed that age younger than 60 years, the presence of varicose veins of the lower extremities, skin cyanosis, syncope in the debut of PE were independent clinical factors that significantly influence the doctor's decision to perform thrombolysis. Increased troponin I, right ventricular dysfunction, and the severity of PE according to the PESI score showed no significant impact on this decision. In-hospital mortality in the group 2 was 1.9% (5 patients), while there were no deaths in the group 1. But the analysis of the association of thrombolysis with survival was difficult to perform due to the low incidence of deaths and the small number of patients in the group with thrombolysis (odds ratio 0.34; 95% confidence interval 0.03-8.18; р=0.856). No major bleeding was registered in any group.Conclusion. We were not able to clearly identify independent clinical or instrumental factors that influence the decision to perform thrombolysis in patients with PE outside the framework of evidence-based medicine. Further research is needed.